DECREASING pH, PROXIMATE (WATER, PROTEIN AND SUGAR) AND β-CAROTENE CONTENT OF KABOCHA YELLOW PUMPKIN (Cucurbita Maxima L.) WERE INFLUENCED BY AIR COOLING AND VACUUM COOLING STORAGE - Triana Kusumaningsih; Tri Martini; Lestari Okstafiyanti; Kartika Setia Rini (UNIVERSITAS SEBELAS MARET (UNS), 2017)
ABSTRACTThe aim of the research is to determine the effective storage technique between the air cooling and vacuum cooling technique during storage process (0, 4, 8 and 12 weeks) and to increase the shelf life of kabocha pumpkin. Parameters measured during storage process were β-carotene and proximate content (water, pH, protein and sugar). β-carotene content was analyzed by Spectrophotometer UV-VIS followed by validation method, water content by Gravimetric method, pH by pH meter, protein by Makro Kjehldal method, and sugar by Luff Schrool method. The validation method showed good result which is proved by linearity, accuracy, precission, LOD, LOQ, and recovery values were 0.988, 98.8%, 3.39-7.73%, 0.011 ppm, 0.016 ppm, and 112% respectively. During storage process, β-carotene content was greater decreased on air cooling storage. For proximate content showed that water content was greater decreased on vacuum cooling storage. pH and the protein content was decreased on air cooling or vacuum cooling storage, but on air cooling was greater. Sugar content was increased during eight weeks and decreased on last week. From the result it can be seen that vacuum cooling storage was better technique for kabocha pumpkin. Keyword: β-carotene, air cooling, proximate, vacuum cooling